Running after the clock - Freitas, Catarina (2005)
The way we currently understand vertebrate development is undoubtedly associated with the research undertaken at the “Institut d’Embryologie Cellulaire et Moléculaire” at Nogentsur- Marne during the last decades. Working in this Institute has been a privilege for many junior and senior researchers. Eight years ago, in this stimulating environment, an exciting observation followed by a series of revealing experiments gave rise to a novel field of research. This study provided evidence for the existence of a molecular clock underlying chick somite formation. In this review, we focus on the cascade of studies that have followed this discovery. Thus far, it has been demonstrated that the molecular clock is operating in several vertebrate models namely chick, mouse, zebrafish, frog and medaka, probably functioning to provide cells with multidimensional positional information. Loss and gain of function experiments and detailed gene promoter analyses have proved very useful in understanding how the clock machinery works. Recent data has also led to the fascinating hypothesis that the clock might not be an exclusive property of somitic cells, but rather a mechanism used by a wide range of embryonic tissues. Meanwhile, the clock “keeps ticking” and many questions are still waiting for an answer.